Factors Affecting Consumer Preference Toward Soft Drinks in Nepal - Manandhar, Raju Bhai (Management Dynamics, 2021)
Nowadays, soft drinks are commonly used and are famous all over the world. Product features are focused on promoting soft drinks because they play a vital role in meeting the customers' expectations. The study aimed to measure the relationship between packaging and taste in consumers' preference for soft drinks. The present study is descriptive and analytical. Primary data was the leading source for the survey. The five-point Likert scale questionnaire survey was developed to collect preliminary data. This study targeted customers who had used soft drinks to obtain the necessary data. Three hundred and fifteen respondents were selected within the Kathmandu valley, adopting a convenience sample technique. The study applied tools like mean, standard deviation, independent sample t-test, correlation, and regression to analyze the data. The study found that packaging and taste positively impact consumers' preference for soft drinks. However, packaging has a high association. Gender does not affect consumers' choice and packaging but has an impact on taste. Packaging is the most important feature that adds a plus point to attractiveness. So, the company should re-design the packaging model of the product to meet the consumer's expectations.